Mind Mapping and Grammar Error Correction of High School Students in Vietnam: Current View and Perspectives - Huyen Trang; T. Zhukova; Sona A. Galstian (International Journal of Education and Humanities, 2026)
This article examines the effectiveness of mind mapping as a strategy for improving grammar error correction among high school students in Vietnam. Given that many students still struggle with core grammatical components, the study aims to explore how mind maps can be optimally utilized to support the acquisition of grammar knowledge and enhance students’ accuracy in language use. The research specifically seeks to identify the cognitive and instructional benefits of mind mapping that enable learners to visualize grammatical structures, categorize rules, and minimize common errors. Methodologically, this study employs an extensive literature review and analytical approach, drawing on previous empirical and theoretical research to investigate students’ difficulties in learning grammar and the pedagogical value of mind mapping. In addition, a design-based method was applied to systematize perspectives on constructing a structured educational course. This method includes organizing processes and steps needed to integrate mind mapping into grammar instruction effectively. The findings derived from theoretical analysis indicate several key outcomes. First, the study highlights the position of higher educational institutions in Vietnam regarding the integration of mind mapping as a solution to persistent grammatical errors, particularly those related to tenses, articles, and prepositions. Second, it proposes a detailed framework for an educational course aimed at addressing challenges in mind mapping application and grammar error correction among Vietnamese high school students. Third, it formulates essential research questions that guide further investigation into the use of mind maps in improving grammatical accuracy at the tertiary level. In conclusion, the study clarifies the developmental prospects of mind mapping as an effective learning tool for grammar improvement. Integrating mind maps across different stages of instruction and using them as supplementary learning materials can significantly enhance students’ error correction skills. The findings offer a foundation for future research and serve as practical input for designing educational programs that strengthen grammar competence within the Vietnamese and Russian higher education contexts